(untitled) - Ellis, Charles D. (Hoboken, N.J., 2006)
Charley Ellis has written a magnificent portrait, capturing the indomitable spirit of Joe Wilson and his instinctive understanding of the need for and commercial usefulness of a transforming imaging technology. Joe Wilson and his extraordinary team, which I had the good fortune to first meet in 1960, epitomized the wonderful observation of George Bernard Shaw who said, 'Some look at things that are, and ask why? I dream of things that never were and ask why not?
Keywords: Copying machine industry; History; United States